2021
DOI: 10.1002/adfm.202109969
|View full text |Cite
|
Sign up to set email alerts
|

Boosting K+ Capacitive Storage in Dual‐Doped Carbon Crumples with B–N Moiety via a General Protic‐Salt Synthetic Strategy

Abstract: The heteroatom co-doped carbonaceous anodes have readily attracted great attention in potassium-ion batteries (PIBs), owing to their augmented carbon interlayer distances and increased K + storage sites to induce enhanced capacity value. Nevertheless, the synergistic effect of dual-doped heteroatoms is still unclear and lacks systematic explorations. In addition, traditional synthetic routes are cumbersome with template removal step, which are normally deficient in product scalability. Herein, a generic protic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 51 publications
(58 reference statements)
2
33
0
Order By: Relevance
“…Figure S13, Supporting Information, shows the EIS profiles of two electrodes, where the CoS 2 -CNs electrode exhibits a lower charge-transfer resistance (Rct) value than bare CoS 2 , revealing the higher charge transfer ability and electronic conductivity of CoS 2 -CNs. [22] Based on the CV, GITT, and EIS results, it can be concluded that the carbon matrix can effectively improve K + transportation in the whole structure, thus leading to the enhanced rate capability of CoS 2 -CNs electrodes (as shown in Figure 2d), also consistent with the above DFT-based analysis.…”
Section: Resultssupporting
confidence: 78%
“…Figure S13, Supporting Information, shows the EIS profiles of two electrodes, where the CoS 2 -CNs electrode exhibits a lower charge-transfer resistance (Rct) value than bare CoS 2 , revealing the higher charge transfer ability and electronic conductivity of CoS 2 -CNs. [22] Based on the CV, GITT, and EIS results, it can be concluded that the carbon matrix can effectively improve K + transportation in the whole structure, thus leading to the enhanced rate capability of CoS 2 -CNs electrodes (as shown in Figure 2d), also consistent with the above DFT-based analysis.…”
Section: Resultssupporting
confidence: 78%
“…Schematic of enhancing ion adsorption as the decider. Reprinted with permission from ref . Copyright 2022 Wiley-VCH.…”
Section: Versatility and Essentiality Of Direct-cvd-enabled Graphenementioning
confidence: 99%
“…Aside from the successful application in Li-ion batteries, graphene has recently received growing research attention in the emerging K-ion batteries, wherein the dopants are evidenced to enhance the affinity with K + and hence improve the storage capability. Nevertheless, the dual-doping configuration in graphene has rarely been explored by far. , Furthermore, the pragmatic strategies to achieve in-target and large-scale synthesis of graphene are still lacking. To this end, Lu et al revealed that N/S dual-doped graphene (denoted as NSG) with ample potassiophilic surface moieties can significantly boost the K-ion adsorption in comparison with nondoped and single-doped graphene with the aid of theoretical predictions (Figure a) .…”
Section: Versatility and Essentiality Of Direct-cvd-enabled Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Particularly, it is widely accepted that capacitive behavior mainly takes place at surface or near surface region, [14][15][16] which benefits fast reaction kinetics while protecting the bulk electrode structure from collapse, leading to improved rate capability and cycling stability. Furthermore, capacitive behavior has been demonstrated to be closely related to defects level in active materials; accordingly, many efforts have been devoted to regulating the microstructure or configuration of carbon with the aim of obtaining abundant defects toward high capacitive contribution, [17][18][19] in which heteroatom doping (including F, N, P, S, etc.) is the most attractive method to boost K-adsorption capability.…”
mentioning
confidence: 99%